2019
DOI: 10.1108/jsocm-01-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the effectiveness of advertisements targeting social issues in least developed countries

Abstract: Purpose The purpose of this paper is to explore the application of advertising variation and repetition strategies in the context of communicating about social issues in least developed countries (LDCs). Design/methodology/approach Study 1 used a between-subjects experimental study using 106 students which were exposed to either the varied advertising condition (a negative appeal followed by a positive appeal or vice versa) or repetition condition (two negative appeals). In Study 2, a total of 111 students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The use of a negative to positive emotional flow or a threat–relief emotional message is hypothesized to result in a stronger persuasion outcome [ 49 ]. A recent study by Gebreselassie Andinet and Bougie [ 67 ] found the flow from negative to positive appeals produced more desirable results than negative or positive appeals alone. Similarly, Rossiter and Thornton [ 68 ] found fear–relief appeals to reduce young adults’ speed choice when driving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of a negative to positive emotional flow or a threat–relief emotional message is hypothesized to result in a stronger persuasion outcome [ 49 ]. A recent study by Gebreselassie Andinet and Bougie [ 67 ] found the flow from negative to positive appeals produced more desirable results than negative or positive appeals alone. Similarly, Rossiter and Thornton [ 68 ] found fear–relief appeals to reduce young adults’ speed choice when driving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, marketers may adopt a strategy by which consumers are repeatedly exposed to mobile ads with limited interruption, with ample variations in execution to evade irritation and annoyance (Błachnio et al, 2018;Försch & De Haan, 2018). Further, advertising-variation strategies have been shown to be more effective in terms of recall and thus can be useful tools for marketers in that they can lead to synergistic effects (Gebreselassie & Bougie, 2019). Thirdly, managers must balance marketing campaigns to leverage the benefits of mobile ads and evade their consequential effects.…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…Highlighting the consequences of specific actions have been demonstrated as effective for reinforcing sustainable behavior (Anghelcev and Sar, 2014), especially in the context of green advertising and green attitudes and buying intention among young adults (Suci et al ., 2022). Furthermore, the combination of a negative appeal followed by a positive appeal demonstrates its effectiveness in the context of social marketing aimed at addressing social issues (Gebreselassie and Bougie, 2019). Self-other framing considers perceiving benefits for the self and for the others (Trope and Liberman, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%